TC4 titanium alloy surface gradient nanostructure construction method based on high-temperature ultrasonic rolling

By constructing a gradient nanostructure on the surface of TC4 titanium alloy using high-temperature ultrasonic rolling technology, the problem of insufficient fatigue resistance of TC4 titanium alloy is solved, achieving efficient and economical improvement of material properties, which is suitable for long-term service of high-temperature components of aero-engines.

CN120989542APending Publication Date: 2025-11-21SHENYANG LIMING AERO-ENGINE GROUP CORPORATION
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511215259.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively improve the fatigue resistance and fretting fatigue resistance of TC4 titanium alloys, and existing methods are either costly or result in uneven processing, failing to meet the long-term service requirements of high-temperature components in aero-engines.

Method used

A gradient nanostructure was constructed on the surface of TC4 titanium alloy using high-temperature ultrasonic rolling technology. Through thermo-mechanical coupling, the surface microstructure of the material was reconstructed in a controllable manner, including the gradient distribution of the surface nanocrystalline region, transition layer and matrix layer. Grain refinement was achieved by utilizing dislocation slip, twinning coordination and dynamic recrystallization mechanisms.

Benefits of technology

Significantly improves the fatigue resistance and fretting fatigue resistance of TC4 titanium alloy in high-temperature environments, reduces equipment investment and energy consumption, is suitable for uniform processing of complex curved surface components, and meets the performance requirements of high-temperature components of aero-engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120989542A_ABST
    Figure CN120989542A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal material surface strengthening, in particular to a TC4 titanium alloy surface gradient nanostructure construction method based on high-temperature ultrasonic rolling, which comprises the following steps: constructing a thickness-controllable gradient nanostructure layer on a TC4 titanium alloy surface through a thermal-mechanical coupling effect, refining surface grains to be less than 100nm, forming submicron transition grains on a subsurface layer, and forming a gradient nanostructure on the surface of the TC4 titanium alloy. And the core part retains a coarse grain structure. According to the method, the fatigue resistance, fretting fatigue resistance and high-temperature creep resistance of the TC4 titanium alloy can be remarkably improved, meanwhile, the equipment cost and energy consumption are reduced, and the method is suitable for aero-engine manufacturing and overhaul environments and has the high industrialization advantage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface strengthening technology of metallic materials, specifically relating to a method for constructing gradient nanostructures on the surface of TC4 titanium alloy based on high-temperature ultrasonic rolling. Background Technology

[0002] Key components of aero-engines, such as compressor blades, operate under complex conditions of high temperatures (500-600℃), high-cycle alternating loads, and oxidative corrosion for extended periods, placing extremely high demands on material properties. TC4 titanium alloy, due to its excellent specific strength and good overall performance, is widely used in high-temperature components of aero-engines. However, the inherent characteristics of TC4 titanium alloy, such as its low surface hardness and high coefficient of friction, make it prone to failure problems in practical applications, such as fretting fatigue in blade tenons and blade fatigue crack initiation, which greatly limits its service life and reliability. Therefore, how to effectively improve the fatigue resistance and fretting fatigue resistance of TC4 titanium alloy has become an urgent technical challenge.

[0003] Currently, the aero-engine manufacturing industry primarily uses two techniques to improve the fatigue performance of TC4 titanium alloys: mechanical shot peening and laser shock peening. However, these techniques have significant limitations. While mechanical shot peening can refine the surface grains to some extent, its effect is limited, with grain sizes typically exceeding 100 nm and insufficient residual compressive stress layer depth, generally less than 200 μm. Under high-temperature conditions, the stress relaxation rate exceeds 40%, making it difficult to meet the requirements for long-term high-temperature service. Laser shock peening, although capable of achieving a deeper residual compressive stress layer, suffers from high equipment costs, poor uniformity in processing curved components, and the potential for surface remelting defects, affecting the material's surface integrity and performance stability. Therefore, developing a novel surface strengthening technology to overcome the shortcomings of existing technologies is crucial for improving the performance of TC4 titanium alloys. Summary of the Invention

[0004] To address the aforementioned problems, this invention proposes a method for constructing gradient nanostructures on the surface of TC4 titanium alloy based on high-temperature ultrasonic rolling. The aim is to achieve controllable reconstruction of the surface microstructure of TC4 titanium alloy through thermo-mechanical coupling, thereby significantly improving its fatigue resistance and fretting fatigue resistance, while also considering the economic feasibility and industrial application. This technology not only overcomes the limitations of existing technologies but also provides a novel solution for improving the performance of high-temperature components in aero-engines.

[0005] The technical solution of this invention is: A method for constructing gradient nanostructures on the surface of TC4 titanium alloy based on high-temperature ultrasonic rolling includes the following steps: Pretreatment: Polishing removes tool marks and the original oxide layer from the TC4 titanium alloy surface, making the surface roughness Ra≤0.8μm; Clamping and positioning: The workpiece is fixed using a ceramic-based special fixture; Heating: The workpiece is heated to 450±10℃ using an induction coil; Rolling operation: Turn on the ultrasonic rolling equipment and use a 10mm diameter carbide ball tool head to perform two rolling processes. The process parameters are: ultrasonic frequency 30kHz, static pressure 400±50N, amplitude 20±2μm, feed speed 0.1mm / r, spindle speed 300r / min, and pass overlap rate controlled at 40%; Post-treatment: air cool to room temperature; By combining ultrasonic high-frequency impact with static pressure, and through the coordinated effects of dislocation slip, twinning, and dynamic recrystallization at high temperatures, the surface structure of the material can be reconstructed in a controllable manner.

[0006] Furthermore, in the above method, the gradient nanostructure, from the surface to the inside, is as follows: Surface nanocrystalline region: grain size <100nm, forming a nanocrystalline layer with high hardness and excellent fatigue resistance, which can effectively resist wear and fretting fatigue; Transition layer: dislocation tangles and submicron structure, with grain size between nanoscale and original coarse grains, plays a transitional role, relieves stress concentration and inhibits crack propagation; Matrix layer: Undeformed coarse-grained structure, retaining the toughness and plasticity of the material, ensuring the stability of the overall structure.

[0007] Furthermore, in the above method, the ceramic-based special fixture is made of a ceramic-based composite material with a low coefficient of thermal expansion.

[0008] The design concept of this application is: During the high-temperature ultrasonic rolling process at 450±10℃, thermo-mechanical coupling achieves the construction of gradient nanostructures through the following synergistic mechanism: I. Dislocation slip dominates plastic deformation. High-temperature environments significantly reduce the stacking fault energy of TC4 titanium alloys, promoting dislocation cross-slip and climb. The static pressure (400±50N) of ultrasonic rolling induces a large number of dislocations to multiply, forming high-density dislocation walls, which provide a basis for nanocrystallization.

[0009] II. Coordinated Strain Distribution of Twins. The close-packed hexaburr structure of TC4 titanium alloy activates {10-12} tensile twins under impact load. High-frequency ultrasonic impact (30kHz) induces twin lamellae, splits the original coarse grains, stores deformation energy, and accelerates the grain refinement process.

[0010] III. Dynamic recrystallization completes nano-sizing. The continuous high temperature during ultrasonic rolling triggers continuous dynamic recrystallization, which promotes the reorganization of dislocation cells to form subgrain boundaries. The subgrain boundaries absorb dislocations and transform them into large-angle grain boundaries, which ultimately form equiaxed nanocrystals through grain boundary migration.

[0011] In summary, the thermo-mechanical coupling effect significantly improves the grain refinement efficiency compared to room temperature, while avoiding microcracks caused by low-temperature rolling.

[0012] Advantages and beneficial effects of the present invention: 1. This invention utilizes thermo-mechanical coupling to construct a gradient nanostructure on the surface of TC4 titanium alloy, significantly improving the material's fatigue resistance, fretting fatigue resistance, and high-temperature creep resistance under both room temperature and high-temperature environments. Specifically, the surface layer possesses high hardness and excellent fatigue resistance, effectively resisting wear and fretting fatigue; the transition layer acts as a transition layer, alleviating stress concentration and inhibiting crack propagation; and the matrix layer retains the material's toughness and plasticity, ensuring the overall structural stability.

[0013] 2. The irreplaceable effect of thermo-mechanical coupling: High-temperature heat treatment alone can only restore dislocation structures and cannot achieve grain refinement; ultrasonic rolling at room temperature alone is prone to generating microcracks. The thermo-mechanical coupling of this invention has synergistic advantages: high-temperature thermal activation promotes dislocation movement, and ultrasonic rolling mechanical energy intensifies dislocation movement and triggers twinning, ultimately achieving self-organized gradient nano-sizing through dynamic recrystallization.

[0014] 3. Compared with laser shock peening technology, this invention significantly reduces equipment investment and energy consumption, and can be integrated into five-axis CNC machine tools, making it suitable for aero-engine manufacturing and overhaul environments.

[0015] 4. This invention is applicable to the surface treatment of complex curved components, exhibiting high processing uniformity and reliability. By precisely controlling key process parameters such as rolling temperature, static pressure, ultrasonic amplitude, feed rate, spindle speed, and pass overlap rate, the accurate construction of gradient nanostructures is ensured.

[0016] 5. This invention achieves controllable reconstruction of the surface structure of materials through the synergistic effect of an induction heating device and an ultrasonic rolling system, thereby meeting the performance requirements of high-temperature components of aero-engines under extreme operating conditions.

[0017] In summary, this invention provides an efficient, economical, and easily industrialized method for surface strengthening of TC4 titanium alloy, providing important technical support for improving the performance of high-temperature components in aero-engines. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the method for constructing gradient nanostructures on the surface of TC4 titanium alloy according to the present invention; Figure 2 This is an EBSD image of the surface layer of the TC4 titanium alloy high-temperature ultrasonic rolling sample from Example 1 of the present invention. Figure 3 This is a TEM image of the nanocrystalline region on the surface of the TC4 titanium alloy high-temperature ultrasonic rolling sample in Example 1 of this invention. Figure 4 This is a TEM image of the submicron crystalline layer of the TC4 titanium alloy high-temperature ultrasonic rolling sample in Example 1 of the present invention; Figure 5 This is a TEM image of the original coarse-grained layer of the TC4 titanium alloy high-temperature ultrasonic rolling sample in Example 1 of the present invention; Figure 6 The fatigue specimen dimensions and fatigue life of the original and high-temperature ultrasonically rolled TC4 titanium alloy specimens in Example 1 of this invention are shown. Detailed Implementation

[0019] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings. The following embodiments are for illustrative purposes only and should not be used to limit the scope of the present invention.

[0020] Example 1

[0021] This embodiment describes a method for constructing a surface gradient nanostructure for compressor blades, specifically including the following steps: Pretreatment: Polishing removes surface tool marks and the original oxide layer from the T compressor blades, making the surface roughness Ra≤0.8μm; Clamping and positioning: The workpiece is fixed using a ceramic-based special fixture; the silicon nitride (Si3N4) ceramic-based special fixture is made of a ceramic-based composite material with a low coefficient of thermal expansion; Heating: The workpiece is heated to 450℃ using an induction coil; Rolling operation: such as Figure 1 As shown, the ultrasonic rolling equipment is turned on, and two rolling processes are performed using a 10mm diameter carbide ball tool head. The process parameters are: ultrasonic frequency 30kHz, static pressure 400N, amplitude 20μm, feed speed 0.1mm / r, spindle speed 300r / min, and pass overlap rate controlled at 40%. Post-treatment: Air-cool to room temperature; like Figure 2 As shown, the gradient nanostructure on the blade surface, from the surface inwards, is as follows: Surface nanocrystalline region: grain size <100nm; Submicron crystalline layers: dislocation entanglement and submicron-scale structure; Original coarse-grained layer: Undeformed coarse-grained structure.

[0022] Figure 3 (a) is a selected area electron diffraction pattern of the blade surface after high-temperature ultrasonic rolling strengthening. The image is ring-shaped, indicating that disordered nanocrystals are formed on the blade surface after high-temperature ultrasonic rolling strengthening. Figure 3 (b) is a transmission electron microscope (TEM) bright-field image of the blade surface after high-temperature ultrasonic rolling strengthening. The TEM bright-field image shows that the size of the nanocrystals is less than 100 nm, which is consistent with the EBSD data.

[0023] Figure 4 (a) and Figure 4 (b) is a TEM bright-field image of the submicron crystalline layer of the blade after high-temperature ultrasonic rolling strengthening. Figure 4 (a) shows a large number of dislocation entanglements. From Figure 4 (b) shows a large number of banded microstructures, which are {10-12} tensile twins formed in the close-packed hexagonal phase of TV4 titanium alloy.

[0024] Figure 5 The image is a bright-field TEM image of the original coarse grains, which is corroborated by EBSD data.

[0025] Fatigue test: The fatigue test specimen is a dog bone shaped specimen, with dimensions as follows: Figure 6 As shown in (a), two sets of fatigue tests were conducted. The first set consisted of the original specimens, which served as a reference group. The second set consisted of specimens that had undergone high-temperature ultrasonic rolling strengthening. Both sets of fatigue specimens were ground using sandpaper with different roughnesses to achieve a surface condition similar to that of actual compressor blades. To prevent fatigue cracks from arising from transverse scratches, grinding was always performed along the axial direction of the specimen. All fatigue tests were conducted under tensile-tensile constant amplitude axial load control, with a sine wave waveform at a frequency of 15 Hz, a stress ratio (minimum to maximum stress ratio) of 0.1, and a maximum axial volumetric stress of 600 MPa. To ensure the reliability of the results, each set of specimens underwent at least three repeated tests. All fatigue tests were conducted using a 250 kN servo-hydraulic fatigue tester, MTS-Landmark 370.25, under atmospheric conditions and at room temperature.

[0026] Example 2

[0027] The difference between this embodiment and Embodiment 1 is that: During the heating process, the workpiece is heated to 440°C using an induction coil; During the rolling operation, the static pressure is 450N and the amplitude is 18μm.

[0028] Example 3

[0029] The difference between this embodiment and Embodiment 1 is that: During the heating process, the workpiece is heated to 460°C using an induction coil; During the rolling operation, the static pressure is 460N and the amplitude is 22μm.

Claims

1. A method for constructing gradient nanostructures on the surface of TC4 titanium alloy based on high-temperature ultrasonic rolling, characterized in that, Includes the following steps: Pretreatment: Polishing removes tool marks and the original oxide layer from the TC4 titanium alloy surface, making the surface roughness Ra≤0.8μm; Clamping and positioning: The workpiece is fixed using a ceramic-based special fixture; Heating: The workpiece is heated to 450±10℃ using an induction coil; Rolling operation: Turn on the ultrasonic rolling equipment and use a 10mm diameter carbide ball tool head to perform two rolling processes. The process parameters are: ultrasonic frequency 30kHz, static pressure 400±50N, amplitude 20±2μm, feed speed 0.1mm / r, spindle speed 300r / min, and pass overlap rate controlled at 40%. Post-treatment: Air-cool to room temperature; By combining ultrasonic high-frequency impact with static pressure, and through the coordinated effects of dislocation slip, twinning, and dynamic recrystallization at high temperatures, the surface structure of the material can be reconstructed in a controllable manner.

2. The method according to claim 1, characterized in that, The gradient nanostructure, from the outside in, consists of: Nanocrystalline layer: grain size <100nm; Submicron crystalline layers: dislocation entanglement and submicron-scale structure; Original coarse-grained layer: Undeformed coarse-grained structure.

3. The method according to claim 1, characterized in that, The ceramic-based special clamp is made of a ceramic-based composite material with a low coefficient of thermal expansion.

Citation Information

Cited By

  • TC4 titanium alloy low-temperature diffusion welding method based on double nanocrystallization and high-entropy alloy intermediate layer

    CN121696522A

  • Method for diffusion bonding of tc4 titanium alloy at low temperature based on double nanocrystallization and high-entropy alloy interlayer

    CN121696522B